The investor sentiment endurance index and its forecasting ability. (1st January 2012) - He, Ling T.
Based on a binomial probability distribution model, this paper creates an investor sentiment endurance index which estimates the probability that the high or low stock market price equals the closing price of a trading session. Results of this study indicate that the index has decent forecasting ability. The overall accuracy of eight-quarter rolling forecasts reaches 44.15%. Therefore, the true forecasting model and accuracy ratio developed in this study provide financial professionals with additional analytical tools.